Utilização de um blog como ferramenta educacional para o ensino de energia mecânica no ensino médio - Borges, Mateus Alcântara de Castro (2023)
Understanding that nowadays there is a certain ease of access to the internet, it is noted that, more and more, digital technologies are present in the daily lives of students. This dissertation aims to use the advantages offered by them applying them to the teaching of Physics as a way to obtain a more meaningful learning. An educational tool developed used in the present work was an educational blog called Sr. Fisicista, which provides students with theoretical materials, contextualized texts so that they can see where Physics is applied. In addition, the use of virtual simulations allows students to change physical variables in practice and observe how the analyzed event was affected. This educational product is based on David Ausubel's theory of meaningful learning and consists of the application of three didactic sequences that can be shaped according to the teacher's goals. A tester on the content of mechanical energy and an opinion poll were also applied. Through the results obtained by the answers of the students given in the opinion poll, a partially quantitative analysis and mainly qualitative was made. It can be concluded that the educational product worked presents a great potential to be used as an efficient complementation to the teaching of Physics.